A critical review on microbial carbonate precipitation via denitrification process in building materials. Issue 1 (1st January 2021) - Jain, Surabhi; Fang, Chaolin; Achal, Varenyam
ABSTRACT: The naturally occurring biomineralization or microbially induced calcium carbonate (MICP) precipitation is gaining huge attention due to its widespread application in various fields of engineering. Microbial denitrification is one of the feasible metabolic pathways, in which the denitrifying microbes lead to precipitation of carbonate biomineral by their basic enzymatic and metabolic activities. This review article explains all the metabolic pathways and their mechanism involved in the MICP process in detail along with the benefits of using denitrification over other pathways during MICP implementation. The potential application of denitrification in building materials pertaining to soil reinforcement, bioconcrete, restoration of heritage structures and mitigating the soil pollution has been reviewed by addressing the finding and limitation of MICP treatment. This manuscript further sheds light on the challenges faced during upscaling, real field implementation and the need for future research in this path. The review concludes that although MICP via denitrification is an promising technique to employ it in building materials, a vast interdisciplinary research is still needed for the successful commercialization of this technique.